Trauma-Informed Care on mental health wards: the impact of Power Threat Meaning Framework Team Formulation and Psychological Stabilisation on self-harm and restrictive interventions - Nikopaschos, Faye; Burrell, Gail; Clark, Jordan; Salgueiro, Ana (Frontiers in Psychology, 2023)
Aim The aim of this evaluation was to assess the impact of introducing a model of Trauma-Informed Care (TIC), comprising weekly Power Threat Meaning Framework (PTMF) Team Formulation and weekly Psychological Stabilisation staff training, to a National Health Service (NHS) adult acute inpatient mental health unit over a four-year period. Method A retrospective service evaluation design was employed to assess for differences in the number of incidents of self-harm, seclusion and restraint in the four-year period following the introduction of TIC, when compared to the year prior. Results Significant reductions were demonstrated in the monthly number of incidents of self-harm (p < 0.01; r = 0.42), seclusion (p < 0.05; r = 0.30) and restraint (p < 0.05; d = 0.55) following the introduction of TIC. Conclusion Findings suggest that PTMF Team Formulation and Psychological Stabilisation training can contribute to significant reductions in self-harm and restrictive interventions (seclusion and restraint) on adult mental health wards. Qualitative interviews with staff and service users from the unit will support a better understanding of the mechanisms of this change. Further research, employing a randomised control trial design, could increase the validity and generalisability of findings. However, the ethical implications of withholding potentially beneficial practices from a control group would need to be considered.